PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN BAWANG MEKAH (Eleutherine americana Merr.) TERHADAP KADAR MALONDIALDEHYDE (MDA) TIKUS (Rattus norvegicus) WISTAR JANTAN PASCA PAPARAN ASAP ROKOK - ., Melda Mery Andriyani (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Abstract: Malondialdehyde (MDA) is a biomarker of lipid peroxidation that is closelycorrelated with level of oxidative stress. The aim of this study was to know ethanolextract activities from E.americana leaves against blood plasma MDA in male Wistar ratsexposed by cigarette smoke using tiobarbituric acid test. The simplicia extracted bymaseration using 70% ethanol. Twenty four rats were divided into six groups, i.e. : anormal group, an exposed cigarette smoke (negative) control group, a positive controlgroup and three treatment groups. One normal group received carboxyl methyl celluloseand another groups exposed cigarette smoke during 14 days. Positive control groupreceived vitamin E (18mg/kg BW), and another groups received ethanol extract ofE.americana leaves doses 180; 90; 45mg/kg BW, respectively. The MDA level wasanalysed by spectrophotometer UV-Visible in 532,2 nm. The MDA level staticallyanalysis by Kruskal-Wallis test and following by Mann-Whitney test. The mean MDAlevels of normal group, negative control group, positive control group and groupsreceived ethanol extract of E.americana leaves doses 180; 90; 45mg/kg BW were0,11±0,09; 13,74±2,84; 0,06±0,03; 10,88±2,19; 0,13±0,03; 0,03±0,02 ppm. The meanMDA levels of groups received ethanol extract of E.americana leaves doses at 180; 1 90mg/kg BW significantly (p<0,05) lower than negative control group. These resultsshow the beneficial effect of ethanol extract of E.americana leaves in the MDA levelreducing on the rats that exposed by cigarette. Key words: Eleutherine americana, cigarette smoke, MDA